Enhancing the separation efficiency of a C2H2/C2H4 mixture by a chromium metal–organic framework fabricated via post-synthetic metalation. Issue 4 (8th January 2020) - Yu, Fan; Hu, Bing-Qian; Wang, Xiao-Ning; Zhao, Yu-Meng; Li, Jia-Luo; Li, Bao; Zhou, Hong-Cai
Abstract : A new Cr metal–organic framework was fabricated via post-synthetic metalation, which exhibited enhanced separation performance for C2 H2 /C2 H4 compared to its template of the isostructural Fe framework. Abstract : Chromium metal–organic frameworks (MOFs) are well-known for their stable porous frameworks, which are not fully explored due to the difficulty encountered in the synthesis process. In order to investigate the possibilities of Cr-MOFs as separation materials towards C2 guest molecules, a novel iron MOF was constructed, which could serve as the scaffold to fabricate Cr-MOFs via post-synthetic metalation. The corresponding gas adsorption properties of the two iso-structural MOFs had been systematically investigated, illustrating the potential separation ability of Cr-MOF with respect to CO2 /C2 H2 and C2 H2 /C2 H4 . Furthermore, the real and feasible behaviors of gas separation for Cr-MOF had been verified by dynamic breakthrough experiments. Compared to the iso-structural Fe-MOF, the fabricated Cr-MOF not only improved the chemical stability, but also enhanced the separation efficiency of the C2 gas molecules. The systematic investigation clearly manifests the important role of chromium ions towards the separation of gas molecules and provides other insights into fabricating MOF-based separation materials.